ANALYZING THE NEED OF PROSPECTIVE TOUR GUIDES IN ACQUIRING ENGLISH TO COMMUNICATE WITH FOREIGN TOURISTS IN DESA MENARI AS TOURISM VILLAGE - Elok Widiyati (Proceedings Education and Language International Conference, 2017)
One of the keys to compete in tourism aspect among AEC (Asean Economic Community) members is by raising the capability of tourism human capital. In line with this effort, it is important to make a betterment in teaching English for tour guides. However, sometimes the facilitators ignore their learners’ real need in learning. Here, in the area of EOP (English for Occupational Purposes), as part of ESP (English for Specific Purposes) category, it requires suitable materials during the teaching learning process. Therefore, this study aims to investigate the need of 20 prospective tour guides of Desa Menari, located in Tanon, Ngrawan Village, Getasan Sub Regency, Semarang Regency, Indonesia, where a half of them were teenagers, in experiencing better English. To support the information, there were two college learners as the facilitators. This study belongs to descriptive qualitative. The data was gathered through open questionnaires, interviews, and observation. The result shows that the most of the learners needed to maximize their speaking skill in order to be able in communicating with foreign tourists for example those who came from Singapore, Philippine, Korea, Japan, Egypt, and Italia. Besides, among the language elements, vocabulary became the highest priority to be improved. It is suggested that the recommended materials were greeting, introduction, and purposive conversation dealing with the questions which were commonly delivered by the foreign tourists. To conclude, need analysis is significant to be performed as it will contribute to the learners’ competencies directly and the financial development in the tourism village indirectly.Keyword: EOP-ESP, need analysis, tour guide